Adolescent interviewing skills: effect of feedback. (16th March 2017) - Bourget, Genna; Joukhadar, Nadim; Manos, Sarah; Mann, Karen; Hatchette, Jill; Blake, Kim
Summary: Background: Communicating with adolescent patients can be challenging. Our study assessed the effect of structured feedback following a standardised patient (SP) encounter on postgraduate year‐1 (PGY1) residents' adolescent‐specific communication skills. Communicating with adolescent patients can be challenging Methods: A two‐group, prospective, double‐blind randomised control study design was employed. Measures were taken before and after the intervention. PGY1 residents conducted a 30‐minute interview with an SP adolescent–mother pair, who then individually scored the resident's performance using the validated Structured Communication Adolescent Guide (SCAG). PGY1s were randomised to receive either structured feedback following the interview (feedback group) or no feedback (no feedback group). All residents completed a second interview 4–6 weeks later. Scores were analysed using unpaired t ‐tests. Results: Thirty‐eight residents completed both interviews. The mean total‐item and mean global scores for the first interview did not differ significantly between the feedback ( n = 21) and no‐feedback group ( n = 17). The mean total‐item scores for the feedback group [first interview: 34.19 ± 10.19 (adolescent); 36.33 ± 9.77 (mother)] improved significantly for the second interview [45.17 ± 6.22 (adolescent); 44.71 ± 6.72 (mother); p = 0.002 and 0.003, respectively]. The mean global scores also improved significantly from the first interview [27.00 ± 6.49 (adolescent); 27.47 ± 6.50 (mother)] to the second interview [34.05 ± 3.30 (adolescent); 31.19 ± 3.85 (mother); p = 0.001 and 0.03, respectively]. No significant improvement in the mean total‐item or mean global rating was observed in the no feedback group. Conclusions: Structured feedback following a single adolescent and mother SP encounter resulted in significant improvement in the adolescent‐specific communication skills of PGY1s in performing an adolescent interview.